2016
DOI: 10.4067/s0718-381x2016000200009
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismo (+3954C>T) del Gen IL-1B y su Asociación con la Resorción Radicular Apical Externa Post-Tratamiento Ortodóntico

Abstract: RESUMEN:El objetivo fue determinar la presencia del polimorfismo rs1143634 (+3954C>T) del gen Interleuquina 1 Beta (IL-1B) y su asociación con la resorción radicular apical externa (RRE) post-tratamiento ortodóntico. Se realizó un estudio piloto de individuos tratados con aparatología ortodontica, 13 (casos) presentaron RRE posterior al tratamiento ortodóntico y 22 (controles) estaban clínicamente sanos. A partir de muestras de células epiteliales de mucosa bucal se extrajo ADN y se genotipificó el polimorfism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The Al-Qawasmi et al 5 study in 118 participants found statistically significant differences. On the other hand, Lince 59 found no association in a small sample of 35 subjects. These varying results may be due to differences in treatment protocols, sampling, laboratory analysis and statistical analysis.…”
Section: External Root Resorption (Err) Related To Il-1β Polymorphismmentioning
confidence: 77%
“…The Al-Qawasmi et al 5 study in 118 participants found statistically significant differences. On the other hand, Lince 59 found no association in a small sample of 35 subjects. These varying results may be due to differences in treatment protocols, sampling, laboratory analysis and statistical analysis.…”
Section: External Root Resorption (Err) Related To Il-1β Polymorphismmentioning
confidence: 77%